Bisphosphonate drug holidays: Can we recommend currently? - Vishal R Tandon; Sudhaa Sharma; Annil Mahajan (Journal of Mid-Life Health, 2014)
Bisphosphonates (BP) are the mainstay of treatment for osteoporosis. Subtrochanteric or diaphyseal fractures have been reported with long term use of BP, which raised world-wide debate on two aspects, i.e., for how long the BP is to be given and potential advantages/role of BP drug holidays. BP accumulates in bone with some persistent protective effect after therapy is stopped endorses the concept. Theoretically, a drug holiday may be a considerable option to decrease risks of BP, which continuing the protection from fractures but the level of evidence and data supporting the concept of drug holidays is a week. Hence, no specific recommendations are available on BP drug holidays from major available treatment guidelines on postmenopausal osteoporosis. Hence, before it is recommended it requires more robust research in this field.